Brunner & Suddarth's textbook of medical-surgical nursing - Hinkle, Janice L.; Cheever, Kerry H. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
"This textbook has been a favorite resource for students, instructors, and practicing nurses for almost a half-century. It's comprehensive yet accessible approach covers a broad scope of medical conditions while focusing strongly on the nurse's role in caring for, educating, and assisting patients and families"--Provided by publisher.
Health Care Delivery and Evidence-Based Nursing Practice -- Community-Based Nursing Practice -- Critical Thinking, Ethical Decision Making and the Nursing Process -- Health Education and Promotion -- Adult Health and Nutritional Assessment -- Individual and Family Homeostasis, Stress, and Adaptation -- Overview of Transcultural Nursing -- Overview of Genetics and Genomics in Nursing -- Chronic Illness and Disability -- Principles and Practices of Rehabilitation -- Health Care of the Older Adult -- Pain Management -- Fluid and Electrolytes: Balance and Disturbance -- Shock and Multiple Organ Dysfunction Syndrome -- Oncology: Nursing Management in Cancer Care -- End-of-Life Care -- Preoperative Nursing Management -- Intraoperative Nursing Management -- Postoperative Nursing Management -- Assessment of Respiratory Function -- Respiratory Care Modalities -- Management of Patients With Upper Respiratory Tract Disorders -- Management of Patients With Chest and Lower Respiratory Tract Disorders -- Management of patients with chronic pulmonary disease -- Assessment of cardiovascular function -- Management of patients with coronary vascular disorders -- Management of patients with structural, infectious, and inflammatory cardiac disorders -- Management of patients with complications from heart disease -- Assessment and management of patients with vascular disorders and problems of peripheral circulation -- Assessment and management of patients with hypertension -- Assessment of hematologic function and treatment modalities -- Management of patients with nonmalignant hematologic disorders -- Management of patients with hematologic neoplasms -- Assessment of immune function -- Management of patients with immunodeficiency disorders -- Management of patients with HIV infection and AIDS -- Assessment and management of patients with allergic disorders -- Assessment and management of patients with rheumatic disorders -- Assessment of musculoskeletal function -- Musculoskeletal care modalities -- Management of patients with musculoskeletal disorders -- Management of patients with musculoskeletal trauma -- Assessment of digestive and gastrointestinal function -- Digestive and gastrointestinal treatment modalities -- Management of patients with oral and esophageal disorders -- Management of patients with gastric and duodenal disorders -- Management of patients with intestinal and rectal disorders -- Assessment and management of patients with hepatic disorders -- Assessment and management of patients with biliary disorders -- Assessment and management of patients with diabetes -- Assessment and management of patients with endocrine disorders -- Assessment of kidney and urinary function -- Management of patients with kidney disorders -- Management of patients with urinary disorders -- Assessment and management of female physiologic processes -- Management of patients with female reproductive disorders -- Assessment and management of patients with breast disorders -- Assessment and management of problems related to male reproductive processes -- Assessment of integumentary function -- Management of patients with dermatologic problems -- Management of patients with burn injury -- Assessment and management of patients with eye and vision disorders -- Assessment and management of patients with hearing and balance disorders -- Assessment of neurologic function -- Management of patients with neurologic dysfunction -- Management of patients with cerebrovascular disorders -- Management of patients with neurologic trauma -- Management of patients with neurologic infections, autoimmune disorders, and neuropathies -- Management of patients with oncologic or degenerative neurologic disorders -- Management of patients with infectious diseases -- Emergency nursing -- Terrorism, mass casualty, and disaster nursing.
Preceded by Brunner & Suddarth's textbook of medical-surgical nursing / Suzanne C. Smeltzer [and others]. 12th ed. c2010.
Includes bibliographical references and index.
Keywords: Nursing; Surgical nursing